Identifying novel sphingosine kinase 1 inhibitors as therapeutics against breast cancer - Faez Iqbal Khan; Dakun Lai; Razique Anwer; Iffat Azim; Mohd Kalim Ahmad Khan (Taylor & Francis Group, 2020)
Sphingosine kinase 1 (SphK1) is a promising therapeutic target against several diseases including mammary cancer. The aim of present work is to identify a potent lead compound against breast cancer using ligand-based virtual screening, molecular docking, MD simulations, and the MMPBSA calculations. The LBVS in molecular and virtual libraries yielded 20,800 hits, which were reduced to 621 by several parameters of drug-likeness, lead-likeness, and PAINS. Furthermore, 55 compounds were selected by ADMET descriptors carried forward for molecular interaction studies with SphK1. The binding energy (ΔG) of three screened compounds namely ZINC06823429 (-11.36 kcal/mol), ZINC95421501 (-11.29 kcal/mol), and ZINC95421070 (-11.26 kcal/mol) exhibited stronger than standard drug PF-543 (-9.9 kcal/mol). Finally, it was observed that the ZINC06823429 binds tightly to catalytic site of SphK1 and remain stable during MD simulations. This study provides a significant understanding of SphK1 inhibitors that can be used in the development of potential therapeutics against breast cancer.